Development of an Augmented Reality–Based Science Module Integrated with Mbojo Ethnoscience to Improve Junior High School Students’ Scientific Skills and Environmental Awareness - Syaiful Bakhri; Ika Nurani Dewi; Sutarto (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop and evaluate an Augmented Reality (AR)–based science module integrated with Mbojo ethnoscience to enhance junior high school students’ scientific skills and environmental awareness. The study involved 52 Grade VII students (25 experimental; 27 control) and employed a Research and Development (R&D) method using the ADDIE model combined with a quasi-experimental design. Data were collected through expert validation, student practicality questionnaires, scientific skills tests, and environmental awareness measures, and were analyzed using descriptive statistics and independent-samples t-tests. The module was classified as highly valid (mean = 3.21) and highly practical (89.8% positive responses). The quasi-experimental findings revealed statistically significant improvements in scientific skills (t = 4.215; p < 0.001) and environmental awareness (t = 4.475; p < 0.001) compared to conventional instruction. These findings suggest that the AR–Mbojo ethnoscience module constitutes a valid, practical, and empirically effective instructional innovation for contextual and sustainability-oriented science learning.